How do we know when patients sleep properly or why they do not? - Sjöberg, Folke (BioMed Central, 2013)
The importance of adequate sleep for good health and immune system function is well documented as is reduced sleep quality experienced by ICU patients. In the previous issue of Critical Care, Elliot and co-workers present a well done, largest of its kind, single-center study on sleep patterns in critically ill patients. They base their study on the 'gold standard', the polysomnography technique, which is resource demanding to perform and often difficult to evaluate. The results are especially interesting as the authors not only used polysomnography in a large sample but also, in contrast to others, excluded patients with prior sleep problems. They also recorded patients' subjective sleep experiences in the ICU and thereafter in the ward (validated questionnaires) with simultaneous data collection of factors known to affect sleep in the ICU (mainly treatment interventions, light and sound disturbances). Interestingly, but not surprisingly, sleep was both quantitatively and qualitatively poor. Furthermore, there seemed to be little or no improvement over time when compared to earlier studies. This study stresses the magnitude of the sleep problem despite interventions such as earplugs and/or eyeshades. Sound disturbance was found to be the most significant but improvable factor. The study highlights the challenge and the importance of evaluating sleep in the critical care setting and the present need for alternative methods to measure it. All that in conjunction can be used to solve an important problem for this patient group.